Unearthing Heritage: Empowering High School History Teachers to Illuminate Local Narratives - Setiawan, Iwan; Waheda, Tuan; Conn, Kevin A (Journal of Social Knowledge Education (JSKE), 2024)
Purpose of the study: This research aims to discuss the role of history teachers in local history learning at State 3 Palu high school, the development of local history learning at State 3 Palu high school, and the role of history teachers in local history learning. Methodology:This research is descriptive qualitative research. The sample in this research was high school history teachers with a sampling technique using purposive sampling. Data collection techniques use interviews, observation and documentation. The analysis was carried out using interactive model data analysis. Main Findings: The research results show that in the history learning process, history teachers have carried out their role well. History teachers try to build students' historical awareness by teaching local history of Central Sulawesi and visiting historical sites in the environment around students. Local history is integrated into history subjects so that in implementing learning, history teachers adjust learning plans to the basic competencies specified in curriculum. Adding historical material with local history, especially by utilizing historical sources that are close to the students' environment. History teachers are one of the important elements who must play an active role in developing local history learning. Novelty/Originality of this study: This research provides valuable insight into the role of history teachers in the context of local history learning, with a focus on integration, local resources, and the development of students' historical awareness.